Fault lines in the constitution : the graphic novel : the framers, their fights, and the flaws that affect us today - Levinson, Cynthia; Levinson, Sanford, 1941- (World citizen comics., 2020)
"In 1787, after 116 days of heated debates and bitter arguments, the United States Constitution was created. This imperfect document set forth America's guiding principles, but it would also introduce some of today's most contentious political issues--from gerrymandering, to the Electoral College, to presidential impeachment. With colorful art, compelling discourse, and true stories from America's past and present, Fault Lines in the Constitution: The Graphic Novel sheds light on how today's political struggles have their origins in the decisions of our Founding Fathers"--